Tindakan Penolakan Tokoh Perempuan Sebagai Liyan Dalam Novel Tanah Tabu Karya Anindita S. Thayf - Afni, Mita (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
Abstract Tanah Tabu novel is an inspiring novel or literary work to be read, especially for woman. This novel deservesto be the object of research because it contains the value of the spirit of rationalism, as refelcted by the character Mabel who has a spirit of courage and a high ideology. This study aims to describe the rules of the story and the struggles of female characters through the study of existentialist feminism. Thw method used in this study is a qualitative method, the data contained in the form of a description in the form of words, phrases, sentences and paragraphs to obtain and describe in detail an object. The results of this study explain that in the novel Tanah Tabu tells about the background of life in Papua and the struggle of a woman who experiences oppression due to patriarchal culture. This novel uses a sequential backward plot and does not confuse the reader. It uses a typical Papuan accent and is written from the point of view of a little girl named Leksi, and her two pets, a pig named Kwee and a dog named Pum. The main character in this novel is a woman named Mabel, while the additional female characters are named Mace and Mama Helda. The three female figures dared to act and fight for what should be theirs.